(untitled) (International Journal of Ayurveda and Pharma Research, 2022)
Yonishaithilya is a common gynecological problem of women of contemporary era which has very important impact on female’s sexual function. This must not be taken lightly as they can adversely affect the quality of woman’s life. As per Brihatrayi, Yonishaithilya represents as a symptom of Mahayoni Yonivyapada, Vatala Yonivyapada, Phalini Yonivyapada and Karnini Yonivyapada, not as a separate disease. Etiology, sign, symptoms and treatment of Yonishaithilya resembles with perineal laxity. Perineal laxity is the condition where there is loosening of supporting structure of female pelvis, thereby allowing the descent of one or more pelvic organ through the lax vaginal introitus. Data Source: Brihatrayees and Laghutrayees, also from all contemporary textbooks, Relevant journals and Websites; Review method: Literary review; Objective:. This review article summarizes details of Yonishaithilya, current scientific researches and elaborates the various therapeutic procedure and drug formulations suggested in Ayurveda for the treatment of Yonishaithilya. Scope and Conclusion: Ayurveda gives various Panchakarma and Sthanik chikitsa like local application of Pichu, Snehana Swedana which are economical, easy and nonsurgical; many single plants; herbal formulations used traditionally which gives an eminent result in Yonishaithilya. Untreated Yonishaithilya may produces complications like pelvic organ prolapse, urinary incontinence and may convert into 2nd or 3rd-degree prolapse where conservative treatment is not beneficial. In some cases, a patient has been advised for a hysterectomy but the patient is reluctant to undergo surgery. So, it is preferred to try Ayurvedic medicine which may be the step to avoid hysterectomy. So, it is necessary to treat it as early as possible.